Training and Mentoring on the Development of AI Based Teaching Materials for Social Studies Teachers in Ogan Ilir - Syarifuddin; Sani Safitri; Hudaidah; M. Reza Pahlevi; Tyas Fernanda; M. Taofik Kurrohman; Alif Bahtiar Pamulaan (Pascasarjana Universitas Mataram, 2025)
The training and mentoring program on developing AI based teaching materials in Ogan Ilir aims to enhance the competencies of Social Studies (IPS) teachers in creating innovative and relevant learning resources aligned with current educational technology developments. This program consists of outreach activities, training sessions, and two days of intensive mentoring designed to help teachers utilize artificial intelligence (AI) in designing and producing engaging and interactive digital teaching materials. As an initial step, participants took a pretest to measure their baseline understanding of AI applications in teaching material development. During the training, participants received materials through interactive sessions, group discussions, and hands on practice using various AI tools to create learning content. At the end of the program, a posttest was conducted to evaluate participants’ competency improvement, with the results showing a significant increase in their technopedagogical skills. The program continued with monitoring and evaluation activities to ensure the implementation of the training outcomes in each school. Overall, this activity strengthened the ability of Social Studies teachers to effectively integrate AI in developing teaching materials, thereby improving the quality of the learning process.